Design and synthesis of fused polycycles via Diels–Alder reaction and ring-rearrangement metathesis as key steps - Kotha, Sambasivarao; Ravikumar, Ongolu (Beilstein Journal of Organic Chemistry, 2015)
Atom efficient processes such as the Diels–Alder reaction (DA) and the ring-rearrangement metathesis (RRM) have been used to design new polycycles. In this regard, ruthenium alkylidene catalysts are effective in realizing the RRM of bis-norbornene derivatives prepared by DA reaction and Grignard addition. Here, fused polycycles are assembled which are difficult to produce by conventional synthetic routes.
Keywords: Diels–Alder reaction; Grignard addition; ring-rearrangement metathesis; polycycles